Fate and persistence of DDT and its metabolites in the Okavango Delta, Botswana. - Mbongwe, Bontle. (University of Ottawa (Canada), 2000)
Dichlorodiphenyltrichloroethane (DDT) had been used in the Okavango delta, Botswana, since the 1950's for the control of malaria and sleeping sickness disease vectors. Concentrations of DDT were determined in water, plant material, invertebrates and fish samples. Isotopes of nitrogen (delta15N) were further used to infer organisms' trophic position and the level of biomagnification of total DDT (DDT and it's metabolites). Average concentrations of total DDT ranged from 0.04 ng.L-1 in water to 8.33 ng.g-1 (wet weight) in fish from the Okavango delta. As predicted from global distillation models, these concentrations are about 2 orders of a magnitude lower than the levels in fish from temperate and arctic regions of Canada, where DDT was banned in the early 1970s. The DDE metabolite was the most abundant fraction of total DDT. Although total DDT concentrations were higher in areas treated for malaria control than areas treated for tsetse control, these concentrations were driven by factors other than the historic application of the pesticide. Gaborone dam, an area where DDT had not been used, was sampled in order to compare total DDT levels to treated areas. Here, levels in fish were 3 times higher than in the Okavango delta but consistent with predictions from delta15N values. Lipid was also a significant predictor of DDT concentrations. Fattier and larger fish such as Hydrocynus vittatus and Synodontis sp. contained higher levels of DDT than those with less fat.